Insights on the Dental Evolution of Walruses Based on New Fossil Specimens from California. Issue 5 (1st December 2020) - Biewer, Jacob N.; Velez-Juarbe, Jorge; Parham, James F.
ABSTRACT: Twelve new specimens of fossil walruses are described from four Miocene units in California. The new material represents five taxa: (1) a specimen from the Santa Margarita Formation referred to Imagotaria downsi ; (2) a specimen from the Valmonte Diatomite Member of the Monterey Formation referred to cf. Pontolis magnus ; (3) six specimens from the Monterey Formation referred to a new species of Pontolis ( Pontolis barroni, sp. nov.); (4) one specimen from the Oso Member of the Capistrano Formation referred to a new species of Pontolis ( Pontolis kohnoi, sp. nov.); (5) three specimens from the Oso Member referred to a new genus and species ( Osodobenus eodon, gen. et sp. nov.). A phylogenetic analysis suggests that both the Dusignathinae and an expanded concept of the genus Pontolis represent monophyletic groups. We provide phylogenetic definitions for clade names of odobenids. Two of the new species are represented by specimens of males, females, and juveniles. Analysis of these specimens shows that the dental anatomy of later diverging basal odobenids is more variable than previously considered. The specific pattern of variation is lineage specific and likely corresponds to the intermediate dental morphology of late Miocene odobenids. Osodobenus eodon, gen. et sp. nov., is the first basal odobenid with tusk-like canines, a longitudinally arched palate, and an enlarged infraorbital foramen. These features are plausibly correlated with benthic suction feeding in the odobenins (Pliocene to Recent) and so Os. eodon may represent a case of convergent evolution of benthic feeding in the late Miocene. http://zoobank.org/urn:lsid:zoobank.org:pub:530A114B-46E9-4E6F-A847-8B17FAFD4327